2003
DOI: 10.4049/jimmunol.170.6.3171
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell (DC)-Based Protection Against an Intracellular Pathogen Is Dependent Upon DC-Derived IL-12 and Can Be Induced by Molecularly Defined Antigens

Abstract: Upon loading with microbial Ag and adoptive transfer, dendritic cells (DC) are able to induce immunity to infections. This offers encouragement for the development of DC-based vaccination strategies. However, the mechanisms underlying the adjuvant effect of DC are not fully understood, and there is a need to identify Ag with which to arm DC. In the present study, we analyzed the role of DC-derived IL-12 in the induction of resistance to Leishmania major, and we evaluated the protective efficacy of DC loaded wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 58 publications
3
93
1
1
Order By: Relevance
“…The differentiation of naïve CD4 + T cells into IFN-γ-producing Th1 cells is regulated in part by the nature of costimulatory molecules expressed on APCs and their cytokine milieu [27,28]. Indeed, the production of IL-12 by infected DCs and the degree of responsiveness of T cells to IL-12 critically affects the outcome of L. major infection in mice [29,30]. We found that BMDCs from PIP-deficient mice showed lower expression of CD40, CD80, CD86, and MHC class II ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of naïve CD4 + T cells into IFN-γ-producing Th1 cells is regulated in part by the nature of costimulatory molecules expressed on APCs and their cytokine milieu [27,28]. Indeed, the production of IL-12 by infected DCs and the degree of responsiveness of T cells to IL-12 critically affects the outcome of L. major infection in mice [29,30]. We found that BMDCs from PIP-deficient mice showed lower expression of CD40, CD80, CD86, and MHC class II ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…34 The availability of DC-derived IL-12 is a requirement for the development of protective immunity. 38,39 So in our study, the efficacy of HAF-pulsed and/or AdmIL-12-transduced DCs for controlling aspergillosis in vivo was examined. Firstly, our results showed that HAF-pulsed DCs could induce an Aspergillus Ag-specific Th1 response in vivo; this immune response can bear the function for protection against Aspergillus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, DCs have been examined for their capacity to serve as adjuvants and vaccine carriers mediating protection against bacterial, viral, parasitic or fungal pathogens (Moll & Berberich, 2001a, b). For example, DC-based vaccination improved immunity to malaria (Pouniotis et al, 2004), human immunodeficiency virus (Brown et al, 2003), Candida albicans (d 'Ostiani et al, 2000) and Leishmania major (Berberich et al, 2003;Ramirez-Pineda et al, 2004). …”
Section: Introductionmentioning
confidence: 99%